2018
DOI: 10.2478/pjmpe-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and phase synchrony analyses of EEG signals in Mild Cognitive Impairment (MCI): A study of functional brain connectivity

Abstract: This paper presents an EEG study for coherence and phase synchrony in mild cognitive impairment (MCI) subjects. MCI is characterized by cognitive decline, which is an early stage of Alzheimer’s disease (AD). AD is a neurodegenerative disorder with symptoms such as memory loss and cognitive impairment. EEG coherence is a statistical measure of correlation between signals from electrodes spatially separated on the scalp. The magnitude of phase synchrony is expressed in the phase locking value (PLV), a statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Evidence for functional connectivity loss in aMCI, with respect to the control group, during resting state prior to a task, were reported in various previous studies (Gómez et al, 2009;Zeng et al, 2015;Handayani et al, 2018). For instance, the use of PLI during resting state in Zeng et al (2015), showed a significant decrease in lower alpha, upper alpha, and beta bands at both short and long intra-hemispheric connections.…”
Section: Reduction In Functional Connectivity In Amnestic Mild Cognitive Impairmentmentioning
confidence: 68%
“…Evidence for functional connectivity loss in aMCI, with respect to the control group, during resting state prior to a task, were reported in various previous studies (Gómez et al, 2009;Zeng et al, 2015;Handayani et al, 2018). For instance, the use of PLI during resting state in Zeng et al (2015), showed a significant decrease in lower alpha, upper alpha, and beta bands at both short and long intra-hemispheric connections.…”
Section: Reduction In Functional Connectivity In Amnestic Mild Cognitive Impairmentmentioning
confidence: 68%
“…Normally, the coherence in pairs of adjacent electrodes showed higher values. Conversely, the coherence was reduced as a function of the spatial distance between pairs of electrodes (Handayani et al, 2018). Nevertheless, distal coherence for T7-T8 electrode pair showed higher values.…”
Section: Discussionmentioning
confidence: 88%
“…Coherence measurement for the characterization of AD patients were reported in the study [15,[22][23][24][25]. Meanwhile, a phase synchronization study for characterization of AD patients was carried out in the study [26,27]. The results of this study reported that there was a decrease in EEG coherence or synchronization in patients with cognitive impairment related to AD compared to normal/elderly healthy subjects.…”
Section: Related Workmentioning
confidence: 98%